2020
DOI: 10.3390/sym12020186
|View full text |Cite
|
Sign up to set email alerts
|

Patent Automatic Classification Based on Symmetric Hierarchical Convolution Neural Network

Abstract: With the rapid growth of patent applications, it has become an urgent problem to automatically classify the accepted patent application documents accurately and quickly. Most previous patent automatic classification studies are based on feature engineering and traditional machine learning methods like SVM, and some even rely on the knowledge of domain experts, hence they suffer from low accuracy problem and have poor generalization ability. In this paper, we propose a patent automatic classification method via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…RNNs can predict time series and have been used successfully for text normalization, de-identification, and sequence labeling [ 61 , 62 ]. However, RNNs also suffer from low efficiency in multi-classifier settings [ 63 ]. In this report, we proposed a novel network design to extract drug compounds from sentences using a regression loss function (i.e., mean square root error (MSE)).…”
Section: Discussionmentioning
confidence: 99%
“…RNNs can predict time series and have been used successfully for text normalization, de-identification, and sequence labeling [ 61 , 62 ]. However, RNNs also suffer from low efficiency in multi-classifier settings [ 63 ]. In this report, we proposed a novel network design to extract drug compounds from sentences using a regression loss function (i.e., mean square root error (MSE)).…”
Section: Discussionmentioning
confidence: 99%
“…LSTM units realistically represent or simulate the cognitive processes of human behavior, logical development, and neural organization. It is suitable for handling problems that are highly related to time series, such as machine translation, dialogue generation, encoding, and decoding [ 18 ]. The LSTM unit structure is shown in Figure 2 .…”
Section: Methodsmentioning
confidence: 99%
“…DeepPatent performs multi-label classification at the sub-class level getting 75.46% recall at top 4. Likewise, Zhu et al [7] used the Word Embedding technique to segment and vectorize the input data and then a symmetric hierarchical CNN, named PAC-HCNN, to classify patents outperforming traditional RNN. Moreover, Abdelgawad et al [8] compared several recent neural network models and showed that CNNs are a suitable choice for patent classification.…”
Section: Prior Workmentioning
confidence: 99%
“…Last but not least, some researchers tried to identify which parts of a patent document can provide more representative information for classification tasks [15,17]. They showed that the use of technical and background parts extracted from the descriptions section [17], the first claim [15], the title and abstract [6,7], or at most cases, the title, abstract claims and description [8,11,12] are the most useful parts for patent classification.…”
Section: Prior Workmentioning
confidence: 99%
See 1 more Smart Citation